IDENTIFIKASI ZONA MINERAL BIJIH BESI BERDASARKAN PEMODELAN INVERSI 3D MENGGUNAKAN METODE MAGNETIK - Ramadana, Muhammad; Lepong, Piter (GEOSAINS KUTAI BASIN, 2018)
The geomagnetic method is one of the geophysical methods based on measurement of the variation of the intensity of the magnetic field at the Earth's surface caused by the existence of variations have been magnetized objects distribution under the Earth's surface. Added to the results of a study of literature method of gravity as the comparison data to see the structure of the research area on a regional basis. From the results of gravity anomaly values obtained residual (High Pass Filter) using Gaussian filtering of local gravity values obtained range between -25 mGal until 16,1 mGal at a depth of 1,2 km on a regional basis have geological structures that affect the shape of the rock formations in the area of research is the result of the adoption of rock (intrusion) and from the results of magnetic inversion models 3D mineralized zone indication obtained iron ore to the value suseptibilitas range between 0.01 until 0.02556.